A simplified analytical approach for assessing non-linear in plane seismic response of stick-built glass curtain walls. (March 2023) - Caterino, Nicola
Abstract: In the last decades, glass facades are increasingly used for building skin, especially for their pleasant aesthetic look. During recent earthquakes, such systems have often shown significant damages. Sometimes this made the whole building inoperable, even in the case of no structural damage, so causing extensive direct and indirect losses (e.g. due to the downtime). Herein, the author starts from the experience they gained performing laboratory tests and non-linear finite-element models of stick-built glazing systems to give a contribution in the direction of a simplified modeling of the seismic behavior for such components. An approximate analytical method is herein proposed for an expeditious estimate of the non-linear seismic capacity of a glass-aluminum façade system. This tool can be of great use to the professional dealing with the design and preliminary verification of the seismic performance of such a façade, avoiding or, at least, limiting the use of demanding laboratory tests. Some suggestions are also given about its possible use in the framework of code-based applications. Input data are geometry and mechanical parameters of involved materials. The output is a non-linear static pushover curve representing the lateral response of the façade. The step-by-step procedure is first introduced and explained in terms of assumptions and methodological approach, then applied to a commercial case-study façade, previously tested through a 1:1 sample at the ITC-CNR laboratory (Milan, Italy). The simplified model provides a very fine match to the experimental data, so demonstrating its effectiveness.